HUBUNGAN PENGETAHUAN DAN ASUPAN NATRIUM DENGAN PENYAKIT HIPERTENSI DI WILAYAH KERJA PUSKESMAS MEUREUBO - Arbaiyah; T Alamsyah; Mulyani, Itza; Masitah, Ravi (Universitas Cokroaminoto Palopo, 2025)
This study aims to analyze the relationship between knowledge and sodium intake and the incidence of hypertension in the Meureubo Community Health Center (UPT) work area. This study used a descriptive analytical design with a cross-sectional approach. The study population was all hypertension patients visiting the General Clinic of the Meureubo Community Health Center (UPT Puskesmas) (N=1,191), with a sample of 92 respondents selected using accidental sampling. The research instruments included a knowledge questionnaire, a Food Frequency Questionnaire (FFQ) to measure sodium intake, and an observation sheet. Data were analyzed using univariate and bivariate methods using the Chi-Square test with a significance level of α=0.05. The results showed a significant relationship between knowledge level and the incidence of hypertension (p-value = 0.016), as well as a significant relationship between sodium intake and the incidence of hypertension (p-value = 0.014). This suggests that respondents with low knowledge and high sodium intake are at greater risk of developing hypertension. The conclusion of this study is that there is a relationship between knowledge and sodium intake and the incidence of hypertension in the Meureubo Community Health Center (UPT Puskesmas) work area. It is recommended that the Community Health Center increase educational activities related to healthy living behavior and limiting sodium consumption to prevent and control hypertension.